ABS (Acrylonitrile Butadiene Styrene) composite material containing halogen-free flame retardant and preparation process
By using poly(benzimidazole-hydroxyDOPO) halogen-free flame retardant and compatibility agent in ABS materials for blending and modification, the problems of poor flame retardant and compatibility of ABS materials are solved, and excellent flame retardant and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411904287.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The flame retardant performance of ABS materials is poor, and the nitrogen-phosphorus-based halogen-free flame retardant has poor compatibility with ABS, which affects its mechanical properties.
Poly(benzimidazole-hydroxyDOPO) halogen-free flame retardant is used for blending and modification with ABS resin, and the compatibility of the flame retardant and ABS is improved by grafting ABS or styrene-maleic anhydride copolymer as the compatibility agent.
The flame retardant properties of ABS materials were significantly improved, with the ultimate oxygen index reaching 27.8-31.5%, and good mechanical properties were maintained, including tensile strength and elongation at break.
Smart Images

Figure BDA0005204005180000042 
Figure BDA0005204005180000051 
Figure BDA0005204005180000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ABS, and in particular relates to an ABS composite material containing a halogen-free flame retardant and a preparation process. Background Art
[0002] ABS acrylonitrile-butadiene-styrene copolymer has good mechanical properties, strong corrosion resistance, and excellent processing performance. It is widely used in medical devices, instruments, packaging materials, etc. However, ABS resin has poor flame retardancy. In practical applications, when ABS material encounters open flames, it is easy to burn and cause fires. This limits the practical application of ABS in the field of fire retardancy. At present, flame retardants are mainly added to ABS to improve its fire retardancy and flame resistance.
[0003] Flame retardants mainly include phosphorus flame retardants, intumescent flame retardants, bromine-containing halogen flame retardants, etc.; in recent years, the development of environmentally friendly halogen-free flame retardants has been a research trend. Compared with small molecule flame retardants, macromolecular polymer flame retardants have good high temperature resistance, are not easy to thermally decompose during processing, have excellent flame retardant effects, and have broad application prospects in polymer materials. Chinese patent CN116694018B discloses a halogen-free flame retardant modified ABS plastic and its synthesis process, using nitrogen-phosphorus styrene-acrylonitrile copolymer as a halogen-free flame retardant and maleic anhydride grafted ABS as a compatibilizer, which can improve the compatibility between the flame retardant and the ABS plastic matrix, thereby improving the flame retardant properties, tensile strength, and impact strength of the material. Therefore, the development of new polymer-based flame retardants is an effective way to improve the flame retardant properties of ABS materials. Summary of the invention
[0004] The invention solves the problem that ABS has poor flame retardancy and that nitrogen-phosphorus halogen-free flame retardants have poor compatibility with ABS and have a significant impact on its mechanical properties.
[0005] In order to solve the above technical problems, the technical solution of the present invention is: an ABS composite material containing a halogen-free flame retardant, comprising 100 parts by weight of ABS resin, 2-15 parts by weight of poly(benzimidazole-hydroxy DOPO) halogen-free flame retardant, and 0.3-2.5 parts by weight of a compatibilizer.
[0006] Preferably, the preparation process of poly (hydroxy DOPO-benzimidazole) halogen-free flame retardant is as follows:
[0007] 3,6-dibromobenzimidazole-hydroxy DOPO, 1,4-phenylenediboric acid, tetrakis(triphenylphosphine)palladium, N,N-dimethylformamide, potassium carbonate, water were added to a reaction bottle provided with a condenser reflux tube, and nitrogen was introduced to replace the air to carry out a coupling polymerization reaction, water was added to dilute the solution, the solvent was filtered, and the solution was washed with water and ethanol in turn, and dried to obtain a poly(hydroxy DOPO-benzimidazole) halogen-free flame retardant.
[0008] Preferably, the compatibilizer is styrene-maleic anhydride copolymer or maleic anhydride grafted ABS.
[0009] Preferably, the molar ratio of 3,6-dibromobenzimidazole-hydroxy DOPO, 1,4-phenylenediboronic acid, tetrakis(triphenylphosphine)palladium and potassium carbonate is 1:(0.95-1.05):(0.01-0.013):(1.5-1.8).
[0010] Preferably, the volume ratio of N,N-dimethylformamide to water is 1:(0.08-0.1).
[0011] Preferably, the coupling polymerization reaction is carried out at a temperature of 85-100° C. for 24-48 hours.
[0012] Preferably, the preparation process of 3,6-dibromobenzimidazole-hydroxy DOPO is as follows: N,N-dimethylformamide, 4-[(6-oxy-6H-dibenzo(c,e)(1,2)oxyphosphorus hexanes-6-substituted)hydroxymethyl]benzaldehyde, 3,6-dibromo-1,2-phenylenediamine, and sodium bisulfite are added to a reaction bottle provided with a condenser reflux tube in a molar ratio of 1:(1.1-1.3):(1.1-1.3), nitrogen is introduced to replace the air, and a cyclization reaction is carried out at 120-135° C. for 12-24 hours, water is added for dilution, and then dichloromethane is added for extraction, the organic phases are combined, dried with anhydrous sodium sulfate, the filtrate is distilled under reduced pressure, and then separated by silica gel column chromatography to obtain 3,6-dibromobenzimidazole-hydroxy DOPO.
[0013] Preferably, the preparation process of the ABS composite material containing halogen-free flame retardant is as follows: ABS resin, poly (benzimidazole-hydroxy DOPO) halogen-free flame retardant, and compatibilizer are melt-blended in a twin-screw extruder, the temperature of sections 1-6 of the extruder is 170-200°C, and the screw speed is 30-60r / min; after extrusion, the pelletizer is used for pelletizing to obtain an ABS composite material containing halogen-free flame retardant.
[0014] Technical effect: The present invention utilizes 3,6-dibromobenzimidazole-hydroxy DOPO and 1,4-phenylenediboronic acid to carry out Suzuki coupling reaction to obtain a novel polymer-based poly (hydroxy DOPO-benzimidazole) halogen-free flame retardant containing hydroxyl groups, and further uses styrene-maleic anhydride copolymer or maleic anhydride grafted ABS as a compatibilizer to blend and modify ABS. The halogen-free flame retardant contains a DOPO structure, which can be used as an acid source, an imidazole structure as a nitrogen-containing gas source, and a main chain containing a polyaromatic ring structure with a high carbon content, which has high carbon-forming properties and can be used as a carbon source to form an expansion flame retardant system. During combustion, the flame retardant produces phosphoric acid substances and non-flammable gases such as nitrogen, forming an expansion foam carbon layer on the matrix and surface of the ABS material, which can block heat conduction and inhibit oxygen from contacting the ABS matrix, thereby making the ABS material have excellent flame retardancy. In addition, the polyaromatic ring structure with heat resistance in the main chain of the halogen-free flame retardant has a certain effect of improving the thermal decomposition temperature and heat resistance of ABS.
[0015] The present invention uses maleic anhydride grafted ABS or styrene-maleic anhydride copolymer as a compatibilizer, which contains maleic anhydride groups and can react with hydroxyl groups in the poly(benzimidazole-hydroxy DOPO) halogen-free flame retardant, so that the compatibilizer plays a role in increasing the volume of the halogen-free flame retardant and ABS, improves the compatibility between the two, and prevents the halogen-free flame retardant from affecting the mechanical properties of ABS, and can maintain good tensile strength and elongation at break. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.
[0017] According to the method of "Synthesis and Characterization of 4-[(6-Oxy-6H-dibenzo(c,e)(1,2)oxaphosphorus-6-substituted)hydroxymethyl]benzaldehyde" in the journal "Journal of Xihua University (Natural Science Edition)", Vol. 34, No. 6, November 2015: 0.5 mol terephthalaldehyde was added to the reaction bottle, 15 mL of 1,4-dioxane solution containing 0.55 mmol DOPO was added dropwise at 30°C, reacted for 7 hours, filtered after cooling, and recrystallized from ethanol to obtain 4-[(6-Oxy-6H-dibenzo(c,e)(1,2)oxaphosphorus-6-substituted)hydroxymethyl]benzaldehyde. The structural formula is:
[0018] The CAS number of DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) of the present invention is 35948-25-5. The CAS number of 3,6-dibromo-1,2-phenylenediamine is 69272-50-0.
[0019] ABS resin brand GP-35, Dongguan Shenghao Plastic.
[0020] Maleic anhydride grafted ABS model SH002, Dongguan Shenghao Plastic.
[0021] Styrene-maleic anhydride copolymer model PolyscopeXI RAN4000, Shenzhen Yingqun Chemical.
[0022] Example 1
[0023] 200 mL of N,N-dimethylformamide, 60 mmol of 4-[(6-oxy-6H-dibenzo(c,e)(1,2)oxaphosphorus-6-substituted)hydroxymethyl]benzaldehyde, 78 mmol of 3,6-dibromo-1,2-phenylenediamine, and 78 mmol of sodium bisulfite were added to a reaction bottle equipped with a condenser reflux tube, nitrogen was introduced to replace the air, the temperature was raised to 120°C, and the cyclization reaction was carried out for 12 hours, water was added to dilute, and then dichloromethane was added to extract, the organic phases were combined, dried with anhydrous sodium sulfate, the filtrate was distilled under reduced pressure, and then separated by silica gel column chromatography, the eluent was a petroleum ether and ethyl acetate solution with a volume ratio of 3:1, and 3,6-dibromobenzimidazole-hydroxy DOPO was obtained. The yield was 20.62 g, light yellow powder. The reaction formula is as follows:
[0024]
[0025] Add 40 mmol 3,6-dibromobenzimidazole-hydroxy DOPO, 38 mmol 1,4-phenylenediboronic acid, 0.4 mmol tetrakis(triphenylphosphine) palladium, 1500 mL N,N-dimethylformamide, 72 mmol potassium carbonate, 150 mL water to a reaction bottle equipped with a condenser reflux tube, introduce nitrogen to replace the air, heat to 100°C, and perform coupling polymerization for 24 hours. Add water to dilute the solution, filter the solvent, wash with water and ethanol in turn, and dry to obtain poly(hydroxy DOPO-benzimidazole) halogen-free flame retardant. The yield is 11.25 g, yellow powder. The reaction formula is:
[0026]
[0027] 1000g ABS resin, 20g poly(benzimidazole-hydroxy DOPO) halogen-free flame retardant, and 3g compatibilizer maleic anhydride grafted ABS were melt-blended in a twin-screw extruder. The temperatures of sections 1-6 of the extruder were 170°C, 185°C, 190°C, 200°C, 200°C, and 195°C, and the screw speed was 40r / min. After extrusion, the mixture was pelletized by a pelletizer to obtain an ABS composite material containing a halogen-free flame retardant.
[0028] Example 2
[0029] 150 mL of N,N-dimethylformamide, 60 mmol of 4-[(6-oxy-6H-dibenzo(c,e)(1,2)oxaphosphorus-6-substituted)hydroxymethyl]benzaldehyde, 66 mmol of 3,6-dibromo-1,2-phenylenediamine, and 66 mmol of sodium bisulfite were added to a reaction bottle equipped with a condenser reflux tube, nitrogen was introduced to replace the air, the temperature was raised to 135°C, and the cyclization reaction was carried out for 18 hours, water was added to dilute, and then dichloromethane was added to extract, the organic phases were combined, dried with anhydrous sodium sulfate, the filtrate was distilled under reduced pressure, and then separated by silica gel column chromatography, the eluent was a petroleum ether and ethyl acetate solution with a volume ratio of 3:1, and 3,6-dibromobenzimidazole-hydroxy DOPO was obtained. The yield was 22.19 g, light yellow powder.
[0030] Add 40 mmol 3,6-dibromobenzimidazole-hydroxy DOPO, 42 mmol 1,4-phenylenediboronic acid, 0.42 mmol tetrakis(triphenylphosphine)palladium, 1500 mL N,N-dimethylformamide, 66 mmol potassium carbonate, 130 mL water to a reaction bottle equipped with a condenser reflux tube, introduce nitrogen to replace the air, heat to 90°C, perform coupling polymerization for 36 hours, add water to dilute the solution, filter the solvent, wash with water and ethanol in turn, and dry to obtain poly(hydroxy DOPO-benzimidazole) halogen-free flame retardant. Yield 12.46 g, yellow powder.
[0031] 1000g ABS resin, 60g poly(benzimidazole-hydroxy DOPO) halogen-free flame retardant and 9g compatibilizer styrene-maleic anhydride copolymer were melt-blended in a twin-screw extruder. The temperatures of sections 1-6 of the extruder were 170°C, 185°C, 190°C, 200°C, 200°C and 195°C, and the screw speed was 30r / min. After extrusion, the pelletizer was used for pelletizing to obtain an ABS composite material containing a halogen-free flame retardant.
[0032] Example 3
[0033] 200 mL of N,N-dimethylformamide, 60 mmol of 4-[(6-oxy-6H-dibenzo(c,e)(1,2)oxaphosphorus-hexane-6-substituted)hydroxymethyl]benzaldehyde, 72 mmol of 3,6-dibromo-1,2-phenylenediamine, and 78 mmol of sodium bisulfite were added to a reaction bottle equipped with a condenser reflux tube, nitrogen was introduced to replace the air, the temperature was raised to 120°C, and the cyclization reaction was carried out for 24 hours, water was added to dilute, and then dichloromethane was added to extract, the organic phases were combined, dried with anhydrous sodium sulfate, the filtrate was distilled under reduced pressure, and then separated by silica gel column chromatography, the eluent was a petroleum ether and ethyl acetate solution with a volume ratio of 3:1, and 3,6-dibromobenzimidazole-hydroxy DOPO was obtained. The yield was 20.14 g, light yellow powder.
[0034] Add 40 mmol 3,6-dibromobenzimidazole-hydroxy DOPO, 40 mmol 1,4-phenylenediboronic acid, 0.42 mmol tetrakis(triphenylphosphine)palladium, 1500 mL N,N-dimethylformamide, 60 mmol potassium carbonate, 150 mL water to a reaction bottle equipped with a condenser reflux tube, introduce nitrogen to replace the air, heat to 85°C, perform coupling polymerization for 48 hours, add water to dilute the solution, filter the solvent, wash with water and ethanol in turn, and dry to obtain poly(hydroxy DOPO-benzimidazole) halogen-free flame retardant. Yield 12.05 g, yellow powder.
[0035] 1000g ABS resin, 100g poly(benzimidazole-hydroxy DOPO) halogen-free flame retardant, and 16g compatibilizer maleic anhydride grafted ABS were melt-blended in a twin-screw extruder. The temperatures of sections 1-6 of the extruder were 170°C, 185°C, 190°C, 200°C, 200°C, and 195°C, and the screw speed was 60r / min. After extrusion, the mixture was pelletized by a pelletizer to obtain an ABS composite material containing a halogen-free flame retardant.
[0036] Example 4
[0037] 200 mL of N,N-dimethylformamide, 60 mmol of 4-[(6-oxy-6H-dibenzo(c,e)(1,2)oxaphosphorus-6-substituted)hydroxymethyl]benzaldehyde, 72 mmol of 3,6-dibromo-1,2-phenylenediamine, and 72 mmol of sodium bisulfite were added to a reaction bottle equipped with a condenser reflux tube, nitrogen was introduced to replace the air, the temperature was raised to 125°C, and the cyclization reaction was carried out for 18 hours, water was added to dilute, and then dichloromethane was added to extract, the organic phases were combined, dried with anhydrous sodium sulfate, the filtrate was distilled under reduced pressure, and then separated by silica gel column chromatography to obtain 3,6-dibromobenzimidazole-hydroxy DOPO. The yield was 21.58 g, light yellow powder.
[0038] Add 40 mmol 3,6-dibromobenzimidazole-hydroxy DOPO, 40 mmol 1,4-phenylenediboronic acid, 0.42 mmol tetrakis(triphenylphosphine)palladium, 1500 mL N,N-dimethylformamide, 68 mmol potassium carbonate, 120 mL water to a reaction bottle equipped with a condenser reflux tube, introduce nitrogen to replace the air, heat to 85°C, perform coupling polymerization for 36 hours, add water to dilute the solution, filter the solvent, wash with water and ethanol in turn, and dry to obtain poly(hydroxy DOPO-benzimidazole) halogen-free flame retardant. Yield 11.90 g, yellow powder.
[0039] 1000g ABS resin, 150g poly(benzimidazole-hydroxy DOPO) halogen-free flame retardant, and 25g compatibilizer maleic anhydride grafted ABS were melt-blended in a twin-screw extruder. The temperatures of sections 1-6 of the extruder were 170°C, 185°C, 190°C, 200°C, 200°C, and 195°C, and the screw speed was 60r / min. After extrusion, the mixture was pelletized by a pelletizer to obtain an ABS composite material containing a halogen-free flame retardant.
[0040] Comparative Example 1
[0041] The difference between this comparative example and Example 1 is that no poly (benzimidazole-hydroxy DOPO) halogen-free flame retardant is added.
[0042] 1000g ABS resin and 3g compatibilizer maleic anhydride grafted ABS were melt blended in a twin-screw extruder. The temperatures of sections 1-6 of the extruder were 170°C, 185°C, 190°C, 200°C, 200°C, and 195°C, and the screw speed was 40r / min. After extrusion, the pelletizer was used for pelletizing to obtain an ABS composite material containing a halogen-free flame retardant.
[0043] Comparative Example 2
[0044] The difference between this comparative example and Example 1 is that no compatibilizer maleic anhydride is added to graft ABS.
[0045] 1000g ABS resin and 20g poly(benzimidazole-hydroxy DOPO) halogen-free flame retardant are melt-blended in a twin-screw extruder. The temperatures of sections 1-6 of the extruder are 170°C, 185°C, 190°C, 200°C, 200°C, and 195°C, and the screw speed is 40r / min. After extrusion, the mixture is pelletized by a pelletizer to obtain an ABS composite material containing a halogen-free flame retardant.
[0046] Comparative Example 3
[0047] The difference between this comparative example and Example 1 is that 3,6-dibromobenzimidazole-hydroxy DOPO is used instead of the poly(benzimidazole-hydroxy DOPO) halogen-free flame retardant.
[0048] 1000g ABS resin, 20g 3,6-dibromobenzimidazole-hydroxy DOPO, and 3g compatibilizer maleic anhydride grafted ABS were melt-blended in a twin-screw extruder. The temperatures of sections 1-6 of the extruder were 170°C, 185°C, 190°C, 200°C, 200°C, and 195°C, and the screw speed was 40r / min. After extrusion, the pelletizer was used for pelletizing to obtain an ABS composite material containing a halogen-free flame retardant.
[0049] The ABS composite material containing halogen-free flame retardant was made into standard specimens by injection molding machine. The limiting oxygen index of the specimens was tested according to the GB / T2406.1-2008 method. The vertical burning performance of the specimens was tested according to the UL94 method. The tensile properties of the specimens were tested according to the GB / T 1040.1-2018 method.
[0050] The sample was placed in a thermogravimetric analyzer, and the temperature was increased from 30°C to 700°C at a heating rate of 10°C / min under a nitrogen atmosphere to perform a thermogravimetric performance test.
[0051] Table 1 ABS composite material performance test
[0052]
[0053]
[0054] As shown in Table 1, no flame retardant is added to the ABS of Comparative Example 1, the limiting oxygen index is 18.9%, UL94 has no grade, the residual carbon content is only 1.20%, and the flame retardant performance is very poor. The tensile strength is 40.2%, and the elongation at break is 18.6%.
[0055] In each embodiment, poly(benzimidazole-hydroxy DOPO) halogen-free flame retardant and compatibilizer maleic anhydride grafted ABS or styrene-maleic anhydride copolymer are added. The halogen-free flame retardant contains DOPO structure, which can be used as an acid source, imidazole structure as a nitrogen-containing gas source, and the main chain contains a heat-resistant and high-carbon polyaromatic ring structure. It has high carbonization property and can be used as a carbon source to form an expansion flame retardant system. When burned, it produces phosphoric acid substances and non-flammable gases such as nitrogen, forming an expansion foam carbon layer on the ABS material matrix and surface, which can block heat conduction and inhibit the contact of oxygen with the ABS matrix, so that the ABS material has excellent flame retardancy. UL94 reaches V1 to V0 level, and the limiting oxygen index reaches 27.8-31.5%. In addition, the heat-resistant polyaromatic ring structure of the main chain of the halogen-free flame retardant has a certain effect on improving the heat resistance of ABS, and the thermal decomposition temperature (the temperature when the mass loss is 5%) reaches 384.8-389.1℃, which is higher than that of comparative example 1.
[0056] Maleic anhydride grafted ABS or styrene-maleic anhydride copolymer is added as a compatibilizer, which contains maleic anhydride groups and can react with the hydroxyl groups in the poly(benzimidazole-hydroxy DOPO) halogen-free flame retardant, so that the compatibilizer plays a role in increasing the capacity of the halogen-free flame retardant and ABS, improving the compatibility between the two, so that the halogen-free flame retardant will not affect the mechanical properties of ABS, the tensile strength is maintained at 37.8-42.0MPa, and the elongation at break is maintained at 17.8-19.2%, which is very close to the ABS material of Comparative Example 1.
[0057] The limiting oxygen index of the ABS material in Comparative Example 2 also reaches 27.6%, which is higher than that in Comparative Example 1, and the flame retardancy is excellent. However, no compatibilizer maleic anhydride is added to the ABS grafting, and the compatibility of the halogen-free flame retardant and the ABS resin matrix is very poor, which will affect the mechanical properties of the material. The tensile strength is only 35.8MPa, and the elongation at break is 14.7%, which is significantly lower than that in Comparative Example 1.
[0058] Comparative Example 3 uses 3,6-dibromobenzimidazole-hydroxy DOPO as a flame retardant. The flame retardant contains DOPO and imidazole structures, which can form a nitrogen-phosphorus flame retardant. It also contains bromine flame retardant elements, which improve the limiting oxygen index and flame retardant properties of the ABS material. In addition, the flame retardant contains hydroxyl groups, which can react with the anhydride groups of the compatibilizer. The flame retardant is also very compatible with the ABS resin matrix and has little effect on the tensile properties of the ABS material. However, the flame retardant does not contain a polyaromatic ring structure, and its carbon-forming performance is lower than that of the poly(benzimidazole-hydroxy DOPO) halogen-free flame retardant. The high-temperature residual carbon content of the ABS material is 7.65%, which is lower than that of each embodiment. In addition, the flame retardant contains bromine flame retardant elements, which produce bromine-containing substances such as hydrogen bromide during combustion, causing greater pollution.
[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An ABS composite material containing a halogen-free flame retardant, characterized in that: The ABS composite material comprises 100 parts by weight of ABS resin, 2-15 parts by weight of poly(benzimidazole-hydroxy DOPO) halogen-free flame retardant, and 0.3-2.5 parts by weight of compatibilizer; The preparation process of the poly (hydroxy DOPO-benzimidazole) halogen-free flame retardant is as follows: Add 3,6-dibromobenzimidazole-hydroxy DOPO, 1,4-phenylenediboric acid, tetrakis(triphenylphosphine)palladium, N,N-dimethylformamide, potassium carbonate, and water into a reaction bottle provided with a condenser reflux tube, introduce nitrogen to replace the air, perform a coupling polymerization reaction, add water to dilute the solution, filter the solvent, wash, and dry to obtain a poly(hydroxy DOPO-benzimidazole) halogen-free flame retardant; The 3,6-dibromobenzimidazole-hydroxy DOPO has a structural formula as shown in formula (1):
2. The ABS composite material containing a halogen-free flame retardant according to claim 1, characterized in that: The compatibilizer is styrene-maleic anhydride copolymer or maleic anhydride grafted ABS.
3. The ABS composite material containing halogen-free flame retardant according to claim 1, characterized in that: The molar ratio of the 3,6-dibromobenzimidazole-hydroxy DOPO, 1,4-phenylenediboronic acid, tetrakis(triphenylphosphine)palladium and potassium carbonate is 1:(0.95-1.05):(0.01-0.013):(1.5-1.8).
4. The ABS composite material containing halogen-free flame retardant according to claim 1, characterized in that: The volume ratio of the N,N-dimethylformamide to water is 1:(0.08-0.1).
5. The ABS composite material containing halogen-free flame retardant according to claim 1, characterized in that: The coupling polymerization reaction is carried out at a temperature of 85-100° C. for 24-48 hours.
6. The ABS composite material containing a halogen-free flame retardant according to claim 3, characterized in that: The preparation process of the 3,6-dibromobenzimidazole-hydroxy DOPO is as follows: N,N-dimethylformamide, 4-[(6-oxy-6H-dibenzo(c,e)(1,2)oxyphosphorus hexanes-6-substituted)hydroxymethyl]benzaldehyde, 3,6-dibromo-1,2-phenylenediamine, and sodium bisulfite are added to a reaction bottle provided with a condenser reflux tube, nitrogen is introduced to replace the air, a cyclization reaction is carried out, extraction is performed, and silica gel column chromatography is performed to separate to obtain 3,6-dibromobenzimidazole-hydroxy DOPO.
7. The ABS composite material containing a halogen-free flame retardant according to claim 6, characterized in that: The molar ratio of the 4-[(6-oxy-6H-dibenzo(c,e)(1,2)oxaphosphorus hexanes-6-substituted)hydroxymethyl]benzaldehyde, 3,6-dibromo-1,2-phenylenediamine and sodium bisulfite is 1:(1.1-1.3):(1.1-1.3).
8. The ABS composite material containing a halogen-free flame retardant according to claim 6, characterized in that: The cyclization reaction is carried out at 120-135°C for 12-24h.
9. A process for preparing an ABS composite material containing a halogen-free flame retardant as claimed in any one of claims 1 to 8, characterized in that: The preparation process is as follows: ABS resin, poly (benzimidazole-hydroxy DOPO) halogen-free flame retardant and compatibilizer are melt-blended in a twin-screw extruder, the temperature of the extruder 1-6 sections is 170-200° C., and the screw speed is 30-60 r / min; after extrusion, pelletizer is used for pelletizing to obtain an ABS composite material containing halogen-free flame retardant.
Citation Information
Patent Citations
DOPO-based flame retardant containing benzimidazole structure as well as preparation method and application of DOPO-based flame retardant
CN117362347A
Halogen-free, flame-retardant foamed thermoplastic polymer
EP3926001A1